ROLE OF INTERNATIONAL TRADE LIBERALIZATION IN THE ECONOMIC DEVELOPMENT OF THE COUNTRY - Sotvoldiev Alisher Abdumukhtorovich; Tokhtamurotov Akhmadali Muhammadali ugli (Journals Park Publishing, 2023)
In this article, the impact of international trade liberalization on economic growth is considered based on various international trade theories, including the concepts of export subsidy and protectionism, explained with hypothetical examples. At the same time, it is explained why developing countries choose such a path. It also analyzes how current protectionism is justified and how free trade is advocated, and who wins and loses because of it, in indicators and arguments.
Keywords: GDP, free trade, Makhkum's dilemma, Nash equilibrium, infant industry, economic security, trade instruments, tariff, protectionism, Heckscher-Ohlin model.